Exploring the Role of Culture and Gender in the Use of Rational Appeals: A Genre Study of Saudi and Australian Students’ Emails (The International Journal of Educational Sciences and Arts, 2025)
Genre studies have been primarily concerned with identifying professional writing within various contexts, including legal discourse, business settings, and particularly relevant to this study, academic research writing. Research findings thus far have indicated that native Anglo-Saxon English speakers tend to employ more rational appeals than non-native speakers. However, the full range of underlying strategies and factors have not yet been thoroughly explored due to a lack of comparable tasks. This study explores the approaches taken by potential PhD Saudi students (100 participants) and Australian students (20 participants) when emailing their prospective PhD supervisors, specifically with regards to their use of rational appeals in discussing their future PhD research. The results of this study reveal significant differences in gender and culture. In terms of cultural differences, the two groups differed in their use of four particular moves, namely how they discussed their PhD plans, interests, justification and experience. The writing styles that differentiated both groups in their use of rational appeals, as well as broader pedagogical implications, are also discussed.
Keywords: Rational Appeals; Cultural & Gender Differences; Email Communications; Persuasion; Pragmatics & Politeness; Pedagogical Implication